Factors Associated with Non-Adherence to Antihypertensive Medication among Hypertensive Patients in Community - Shrestha, Tirtha Man; Bhusal, Laxman; Raut, Shankar; Ghimire, Rajan; Shrestha, Poonam (Journal of Karnali Academy of Health Sciences, 2019)
Objective: Hypertension is one of the common non-communicable health problems. While pharmacologic intervention is the most efficient way to control hypertension; non-adherence to medication is accounted as a significant cause for complications. This study was to address and to determine the magnitude of non-adherence among hypertensive patients by summarizing the associated risks factors among patients in community level.Method: This is a cross sectional study conducted on hypertensive patients who visited the community health clinic at Dhading, Nepal on 9th and 10th June 2018 using a pre structured questionnaire. Patients were sampled by nonprobability purposive sampling method. Effect of age, gender, marital status, employment, education level, presence of diabetes, cerebrovascular disease, current smoker, and family history of hypertension were analyzed by compliance of antihypertensive drugs using frequency distribution, chi-square test, and logistic regression. For all of the analysis p value